Hip strength and range of motion: Normal values from a professional football league. Issue 4 (April 2017) - Mosler, Andrea B.; Crossley, Kay M.; Thorborg, Kristian; Whiteley, Rod J.; Weir, Adam; Serner, Andreas; Hölmich, Per
Abstract: Objectives: To determine the normal profiles for hip strength and range of motion (ROM) in a professional football league in Qatar, and examine the effect of leg dominance, age, past history of injury, and ethnicity on these profiles. Design: Cross-sectional cohort study. Methods: Participants included 394 asymptomatic, male professional football players, aged 18–40 years. Strength was measured using a hand held dynamometer with an eccentric test in side-lying for hip adduction and abduction, and the squeeze test in supine with 45° hip flexion. Range of motion measures included: hip internal and external rotation in 90° flexion, hip IR in prone, bent knee fall out and hip abduction in side-lying. Demographic information was collected and the effect on the profiles was analysed using linear mixed models with repeated measures. Results: Strength values (mean ± SD) were: adduction = 3.0 ± 0.6 Nm/kg, abduction = 2.6 ± 0.4 Nm/kg, adduction/abduction ratio = 1.2 ± 0.2, Squeeze test = 3.6 ± 0.8 N/kg. Range of motion values: internal rotation in flexion = 32 ± 8°, external rotation = 38 ± 8°, internal rotation in prone = 38 ± 8°, bent knee fall out = 13 ± 4.4 cm, abduction in side-lying = 50 ± 7.3°. Leg dominance had no clinically relevant effect on these profiles. Multivariate analysis demonstrated that age had a minor influence on squeeze strength (−0.03 N/kg/year), external rotation (−0.30°/year) and abduction range (−0.19°/year) but past history of injury, and ethnicity did not. Conclusions: Normal values are documented for hip strength and range of motion that can be used as reference profiles in the clinical assessment, screening, and management of professional football players. Leg dominance, recent past injury history and ethnicity do not need to be accounted for when using these profiles for comparison purposes.